The Role of Long Noncoding RNAs in Central Nervous System and Neurodegenerative Diseases - Wei, Chang-Wei; Luo, Ting; Zou, Shan-Shan; Wu, An-Shi (Frontiers in Behavioral Neuroscience, 2018)
Long noncoding RNAs (lncRNAs) refer to a group of noncoding RNAs (ncRNAs) that has a transcript of more than 200 nucleotides in length in eukaryotic cells. The lncRNAs regulate gene expression at epigenetic, transcriptional, and post-transcriptional levels by multiple action modes. In this review, we describe the diverse roles reported for lncRNAs, and discuss how they could mechanistically be involved in the development of central nervous system (CNS) and neurodegenerative diseases. Further studies on the function of lncRNAs and their mechanism will help deepen our understanding of the development, function, and diseases of the CNS, and provide new ideas for the design and development of some therapeutic drugs.